Effect of an 8-Week Yoga-Based Lifestyle Intervention on Psycho-Neuro-Immune Axis, Disease Activity, and Perceived Quality of Life in Rheumatoid Arthritis Patients: A Randomized Controlled Trial - Gautam, Surabhi; Kumar, Manoj; Kumar, Uma; Dada, Rima (Frontiers in Psychology, 2020)
Various external stressors and environmental challenges lead to the provocation of the immune system in autoimmune diseases like Rheumatoid arthritis (RA). The inappropriate immune response further triggers the cascade of inflammatory changes resulting in precipitation of symptoms and hampers quality of life (QOL). The underlying psycho-somatic component of the disease requires a holistic approach to its treatment dimension rather than the use of pharmacotherapy. The applicability of mind-body interventions has become essential in today's fast-paced life. Yoga, a mind-body technique, alters the mind's capacity to facilitate systemic functioning at multiple organ system levels. Hence, we conducted this study to evaluate the impact of 8 weeks of a yoga-based lifestyle intervention (YBLI) on psycho-neuro-immune markers, gene expression patterns, and quality of life in RA patients on routine medical therapy. A total of 66 patients were randomized into two groups: yoga group or non-yoga group and were assessed for a panel of inflammatory cytokines (IL-6, IL-17A, TNF-α, and TGF-β), mind-body communicative markers (BDNF, DHEAS, β-endorphin, and sirtuin) and transcript levels of various genes (IL-6, TNF-α, NFKB1, TGF- β, and CTLA4). We assessed disease activity and quality of life (QOL) using the DAS28-ESR and WHOQOL-BREF questionnaire, respectively. Yoga group observed significant improvements in the levels of markers, which influenced the psycho-neuro-immune axis (p<0.001) with an estimated effect size from small to medium range. In the yoga group, there was a significant reduction in DAS28-ESR (p<0.001) and improvement seen in the physical health, psychological, social relationships domains (p<0.001) of QOL, except environmental (p>0.05). The yoga group showed downregulation of IL-6, TNF-α, and CTLA4 and upregulation of TGF-β. These results suggest that a decrease in disease activity after yoga practice is associated with a significant reduction in inflammatory cytokines, the elevation of mind-body communicative markers, and normalization of various transcript levels, which improved QOL. Thus the adoption of YBLI improves clinical outcomes of RA, and decreases systemic inflammation by its beneficial effects on psycho-neuro-immune axis and normalization of dysregulated transcripts. Thus YBLI may be favorable for RA patients as an adjunctive therapy.